Sita Jaminan (Conservatoir Beslag) Menurut Herziene Indonesisch Reglement (HIR) Dalam Praktik Dikaitkan Dengan Kepastian Hukum dan Perlindungan Hukum - Agus Surachman (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
Not all Agreements will proceed according to what is promised, often we find that the agreement is not implemented or only partially done, and will make new legal problems, commonly called wanprestasi. Default means to break the promise (not keeping promises), or the absence of an achievement. The settlement of the default case can be done in 2 ways, ie through non-litigation (litigation) or litigation (legal process) process, the default lawsuit accompanied by the confiscation petition (conservatoir beslag) filed by the plaintiff to the Court is often not in accordance with what is expected by Plaintiffs because the rulings are less clear and the consequences of the judgment can not be executed (non-executable). Based on the above description, the author will write a scientific paper in the form of this thesis with the title: